1978
DOI: 10.1525/ae.1978.5.3.02a00050
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation and the expansion of capitalism: the case of the hammock industry of Yucatan

Abstract: Relations of production in the hammock industry of Yucatan, Mexico, are analyzed using Marx's formula for rate of surplus‐value to measure the exploitation of weavers by merchants. It is argued that the concept of exploitation is useful for analyzing societies in which noncapitalist modes of production are being incorporated into the global capitalist system, and that the exchange theory approach dominant in much of economic anthropology has obstructed the understanding of exploitative economic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…3], For detailed data on incomes of selected artisan families seeDurston [1976],Littlefield [1976a or b],and Novelo [1976]. An analysis of the rate of exploitation in the hammock industry is presented inLittlefield, [1978].Downloaded by [Monash University Library] at 07:34 27 September 2014Capitalist Relations of Production…”
mentioning
confidence: 99%
“…3], For detailed data on incomes of selected artisan families seeDurston [1976],Littlefield [1976a or b],and Novelo [1976]. An analysis of the rate of exploitation in the hammock industry is presented inLittlefield, [1978].Downloaded by [Monash University Library] at 07:34 27 September 2014Capitalist Relations of Production…”
mentioning
confidence: 99%
“…These positive functions are countered by the intermediaries' often monopolistic power and willingness to use coercion to maintain their privileged position. Alice Littlefield (1978) suggested that the entry of intermediaries into areas previously dominated by subsistence activities represents the introduction of capitalist exploitation but ignores the important social functions that intermediaries serve. Timothy Finan (1988, 694) noted that "intermediaries commonly employ strate-28 THE GEOGRAPHICAL REVIEW gies of a social content to achieve their economic intent."…”
Section: Intermediaries and The Calakmul Case Studymentioning
confidence: 99%
“…However, unlike the Yucatecan hammock weavers A. Littlefield (1978) describes, for example, women in Kadafan Tutu control the means of production, and it is they who advance goods to the traders, rather than the other way around. In addition, a good part of the money the men make through trade or donkey rental returns to the women in the form of food, clothing, and periodic gifts to wives or secret lovers.…”
Section: Potterymentioning
confidence: 99%
“…This essay builds upon the work of recent students ofPCPn (Littlefield 1978;Verdon 1979;Silver 1981 ). The overall goal is to illustrate that the complexity of changing relationships between local producers and international market forces renders simplistic pronouncements about the exploitation or entrepreneurial potential of PCPn in Africa as a whole premature.…”
Section: Introductionmentioning
confidence: 99%